2015
DOI: 10.1590/1983-1447.2015.01.49133
|View full text |Cite
|
Sign up to set email alerts
|

Profile and motivation for smoking cessation in surgical inpatients

Abstract: The aim of this cross-sectional study was to describe the profile of smokers hospitalized for surgery, and investigate their motivation to quit. The sample consisted of 100 patients recruited from a university hospital in southern Brazil. Data were collected between February and May 2013, and analyzed using descriptive statistics. The sample was predominantly male (n=58; 58%) and had a mean age of 54.5±13.8 years. Seventy-nine (79%) of the participants were white, 38(38%) were married and 67(67%) had primary e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
1
0
2
Order By: Relevance
“…A study showed that hospitalized patients who smoke are motivated and willing to quit smoking because the smoking restrictions in the hospital environment, their health issues and the hospitalization itself force them to think about their smoking habit. However, the results of this study showed that, in the clinical practice, smoking cessation does not occur as expected because hospitalized smokers are not systematically approached (19) . The support of family members and loved ones reinforces the smokers' decision to quit and should therefore be included in the orientation process (20) .…”
Section: Discussionmentioning
confidence: 60%
“…A study showed that hospitalized patients who smoke are motivated and willing to quit smoking because the smoking restrictions in the hospital environment, their health issues and the hospitalization itself force them to think about their smoking habit. However, the results of this study showed that, in the clinical practice, smoking cessation does not occur as expected because hospitalized smokers are not systematically approached (19) . The support of family members and loved ones reinforces the smokers' decision to quit and should therefore be included in the orientation process (20) .…”
Section: Discussionmentioning
confidence: 60%
“…Talvez esse seja um motivo que explique a discrepância tão grande entre o número de indivíduos tabagistas no grupo SUS e no grupo convênios/ particulares. Estudos com diferentes populações, como pacientes cirúrgicos hospitalizados, 15 pacientes psiquiátricos 16 e até mesmo com uma população de moradores de residências escolhidas aleatoriamente 17 apresentaram o mesmo resultado: associação do tabagismo com a baixa renda.…”
Section: Resultsunclassified
“…ΓενικάΣτη βιβλιογραφία υπάρχουν ετερογενείς μελέτες σχετικά με τους τύπους νοσηλευόμενων ασθενών που στρατολογήθηκαν σε ανάλογα προγράμματα διακοπής.Στην πλειονότητα τους οι παρεμβάσεις διακοπής καπνίσματος για νοσηλευόμενους ασθενείς αφορούν σε άτομα με καρδιαγγειακή νόσο (ΚΑΝ) ως διάγνωση εισόδου. Το κάπνισμα τσιγάρων αυξάνει οξέως τη ροή αίματος του μυοκαρδίου σε ηρεμία, μειώνει την εφεδρεία ροής του μυοκαρδίου, μειώνει την αγγειοδιαστολή η οποία εξαρτάται από το ενδοθήλιο και παρεμποδίζει την ενδογενή ινωδόλυση[21,41]. Οι τρέχοντες στρατηγικοί στόχοι της Αμερικανικής Καρδιολογικής Εταιρίας για την προαγωγή της υγείας και τη μείωση της νόσου, κατατάσσουν το κάπνισμα ως τον σημαντικότερο παράγοντα κινδύνου για καρδιαγγειακά νοσήματα και αγγειακά εγκεφαλικά επεισόδια[23].…”
unclassified